1991
DOI: 10.1128/aem.57.11.3163-3170.1991
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Trichoderma reesei Cellobiohydrolase I and Endoglucanase I on Aspen Cellulose by Using Monoclonal Antibody-Colloidal Gold Conjugates

Abstract: Monoclonal antibodies (MAbs) specific for cellobiohydrolase I (CBH I) and endoglucanase I (EG I) were conjugated to 10-and 15-nm colloidal gold particles, respectively. The binding of CBH I and EG I was visualized by utilizing the MAb-colloidal gold probes. The visualization procedure involved immobilization of cellulose microfibrils on copper electron microscopy grids, incubation of the cellulose-coated grids with celiulase(s), binding of MAb-colloidal gold conjugates to cellulase(s), and visualization via tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The types of native and processed celluloses applied in earlier AFM studies, however, were limiting in various ways ( 2 , 7 , 17 20 ). The use of highly crystalline cellulose alone, for instance, does not allow the investigation of an entire cellulase system featuring CBHs and endoglucanases (EGs), with the latter ones being known to preferably attack amorphous areas ( 2 , 9 , 11 , 18 , 21 ). In contrast to previous research, we took a distinct approach involving the dissolution of the microcrystalline cellulose Avicel in the ionic liquid 1-butyl-3-methylimidazolium chloride (BMIMCl) at 100 °C, which, upon cooling, resulted in a gel-like material ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…The types of native and processed celluloses applied in earlier AFM studies, however, were limiting in various ways ( 2 , 7 , 17 20 ). The use of highly crystalline cellulose alone, for instance, does not allow the investigation of an entire cellulase system featuring CBHs and endoglucanases (EGs), with the latter ones being known to preferably attack amorphous areas ( 2 , 9 , 11 , 18 , 21 ). In contrast to previous research, we took a distinct approach involving the dissolution of the microcrystalline cellulose Avicel in the ionic liquid 1-butyl-3-methylimidazolium chloride (BMIMCl) at 100 °C, which, upon cooling, resulted in a gel-like material ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several other TEM studies focused on GH7 enzymes, including those utilizing gold labeling , and labeling with gold-coupled monoclonal antibodies (immuno-EM). , Immuno-EM was utilized to determine that Tr Cel7A and Tr Cel7B preferentially bind to the crystalline and amorphous regions of substrate, respectively …”
Section: Family 7 Glycoside Hydrolasesmentioning
confidence: 99%
“…On the other hand, Nieves et a1. 22 showed that cellulases adsorb on the cellulose surface as aggregated particles. In such a case, protein multilayers may exist on saturated cellulose, hence, the surface area is overestimated.…”
Section: Adsorption Isotherms-surface Area Determinationmentioning
confidence: 99%